Entrepreneurs’ Preferences Towards Online Market Research Packages: А Discrete Choice Analysis - Nikolić, Ognjen (Yugoslav Journal of Operations Research; Vol 34 No 2 (2024)DO - 10.2298/YJOR230815026N, 2023)
Startups have become a buzzword in the last couple of years, and entrepreneurship became career path for a number of people in the world. With all the advances in education and government subsidizing all over the world, still, statistics shows only a small percentage of successful startups. Studies have shown that the one the leading reasons for startup failure is the misreading of market’s needs. The aim of this paper is to determine the approach to market research, knowledge of tools and methods, and preferences towards online market research tools of entrepreneurs by using Discrete Choice Analysis. The research gathered 187 valid responses from a panel of participants working on developing new products and business, using an online survey tool. In the paper it is shown that the most important attributes for entrepreneurs are the price of the market research tool, followed by the level of details in the report generated, with more indepth analysis regarding segmentation, simulations, and Marginal Willingness to Pay in the further chapters. The results of the research imply the need for a market research business model optimized for those starting a new business, focused primarily on detailed reporting and analysis, with the pricing model adjusted to the lack of resources entrepreneurs face at the start of their ventures, which would help them better understand the market-fit at the beginning and raise the statistic of successful startups.